Preharvest Bagging Influences Berry Quality and Phenolic Composition in 'Kureyş' and 'Banaz Kara' Grape Cultivars - Cuhaci, Cigdem; Zengin, Rukiye; Unal, Mehmet Settar; Erdogan, Selim; Turan, Sebahat; Asma, Bayram Murat (Springer, 2025)
Bagging is a crucial practice for achieving high-quality grape production and to enhance the commercial value of the fruit. The present study investigated the effects of bagging on the antioxidant capacity and phenolic composition of the 'Kurey & scedil;' and 'Banaz Kara' grape varieties, which are widely cultivated in Turkey. The fruits were bagged using brown paper bags at the pea-sized development stage. Significant differences were observed between the two varieties in terms of fruit weight, colour, antioxidant capacity, and specific phenolic compounds. In the 'Kurey & scedil;' variety, bagging was found to enhance antioxidant activity. DPPH increased from 1988.43 mg TE/kg to 2212.53 mg TE/kg, while CUPRAC increased from 3774.28 mg TE/kg to 4534.57 mg TE/kg. The rutin content was also significantly higher in bagged samples (1675.21 mu g/g) compared to unbagged samples (1093.66 mu g/g). However, the concentrations of other important phenolic compounds, including isoquercitrin (10,493.84 mu g/g), eriodictyol (15,620.65 mu g/g), and procyanidin B2 (5573.98 mu g/g), were considerably higher in unbagged fruits. This suggests that exposure to light plays a pivotal role in stimulating the accumulation of these compounds. In the 'Banaz Kara' variety, light exposure was associated with an increased accumulation of phenolic compounds and enhanced skin pigmentation. These findings highlight variety-specific responses and emphasize the importance of adapting vineyard management strategies according to grape variety.w
Keywords: Bagging; Chemical composition; Light-induced coloration; Visual fruit quality